ASESMEN AUTENTIK BERBASIS DIGITAL DALAM PEMBELAJARAN AKIDAH AKHLAK: PENGUATAN HASIL BELAJAR DAN SPIRITUALITAS SISWA - David Ricardo; Suwadi (STKIP Subang, 2026)
The digital transformation in education requires assessment systems that not only focus on academic achievement but also contribute to the development of students’ character and spiritual values. In Akidah Akhlak learning, authentic assessment serves as an essential approach because it enables a holistic evaluation of students’ cognitive, affective, and spiritual dimensions. This study aims to analyze the implementation of authentic assessment and its implications for students’ learning outcomes and spiritual attitudes at MAN 1 Kulon Progo. The research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving the principal and Akidah Akhlak teachers selected through purposive sampling. Data analysis was conducted using the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion drawing. The findings reveal that authentic assessment has been systematically implemented through digital-based planning, implementation, evaluation, and reporting processes. The integration of platforms such as Jogja Media Digital (JMD), Quizizz, and Kahoot enhances the effectiveness of assessment practices, student participation, and the quality of reflective learning. In addition to improving learning outcomes, authentic assessment contributes to strengthening students’ discipline, responsibility, and internalization of religious values. This study highlights that digital-based authentic assessment functions not only as a learning evaluation instrument but also as a strategic approach to fostering students’ spiritual character in the era of digital education.